Popular Culture in the Muslim World - Dilnawaz A. Siddiqui (International Institute of Islamic Thought, 1996)
Popular Culture in Medieval Cairo. By Boaz Shoshan. Cambridge, UK and New York Press Syndicate of the University of Cambridge, 1993.148 pp. Struggle and Survival in the Modern Middle East. By Edmund Burke, III (ed.). Berkeley, CA: University of California Press, 1993,400 pp. Living Islam: From Samarkand to Stornoway. By Akbar Ahmed. New York: Facts on File, Inc., 1994.224 pp. One of the many expressions of the postmodernist revolt against the modernist western establishment is said to be its popular culture. The theoretical literature produced across this cultural divide often characterizes it in terms of two extremes: as a supreme expression of the true aspirations of the heretofore underprivileged masses or as a weapon in the hands of the traditionally powerful political, social, and economic elites. The latter use it as a tool with which to manipulate the masses for their own respective agendas. A constant refrain of Hitler invoking Nazi supremacy over all humanity, as well as our own self-serving politicians doing their own thing in the name of the “intelligent and well-informed will of the American people,” are only two of many examples of this instrument’s ubiquitous use. The Multiple Uses of Popular Culture The vast grey area between these two margins includes umpteen other descriptions of popular culture, such as real “texture of our environment” and “adjustive syndrome,” and Matthew Arnold’s “heedless democratization.” In addition, there are such definitions as “banality” (Elliot), “reduction of the individual to basic instincts,” “titillation of the superficial senses” (Whitman), and “an expression denied by persistent puritanism and bourgeois power” (Marx). Leavis also joined Arnold and Elliot in resisting the popular resistance to “authority” found in traditional culture ...